Creating high reliability teams in healthcare through in situ simulation training - William Riley; Elizabeth Lownik; Carmen Parrotta; Kristi Miller RN; Stan Davis (Administrative Sciences, 2011)
The importance of teamwork on patient safety in healthcare has been well established. However, the theory and research of healthcare teams are seriously lacking in clinical application. While conventional team theory assumes that teams are stable and leadership is constant, a growing body of evidence indicates that most healthcare teams are unstable and lack constant leadership. For healthcare organizations to reduce error and ensure patient safety, the true nature of healthcare teams must be better understood. This study presents a taxonomy of healthcare teams and the determinants of high reliability in healthcare teams based on a series of studies undertaken over a five-year period (2005-2010).
Keywords: 350; team formation; In situ simulation; behavior markers; active failures; high reliability; interdisciplinary teams